Association between Red Blood Cell Distribution Width and Pulmonary Function among Iranian Employees - Pouragha, Hamidreza; Ardali, Tayebeh N.; Mehrdad, Ramin; Pouryaghoub, Gholamreza (Current Respiratory Medicine Reviews, 2022)
Background: RDW has been proposed as a routine test and is available as a prognosis for many diseases and disorders, especially respiratory disorders. In this study, we intend to see if the association between pulmonary function and RDW also applies to non-patients. Methods: This study was performed on 800 people including 466 women and 344 men. Participants in the study were staff enrolled in the Tehran University of Medical Sciences cohort [TEC] study. In this study, RDW levels and pulmonary function were assessed. Elderly populations were not included in this study. Results: The results of the univariate analysis showed that normal values versus abnormal values of RDW were significantly associated with pulmonary function index FEV1, FVC, FEV1/FVC in nonpatient individuals. On the other hand, a significant correlation was observed between RDW values and FEV1 index and FEV1/FVC ratio. Based on linear regression, there was an association between RDW and FVC [R2=0.721]. Conclusion: In this study, we found an association between RDW and FVC so we suggest that abnormal RDW may be considered as a sign of pulmonary dysfunction.
Keywords: pulmonary function